Taking decision general theory and its application in the medical assistance field (II) - Luis Alberto Corona Martínez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
This article deals with methods and techniques for assessing and selecting opinions. Among the ones used by the doctors investigation and analysis are used by the doctors and as a most concrete technique the cost-benefit analysis as well as the so called the tree decision in which subjective probabilities are assessed as a qualitative category not as a quantitative one. These methods and techniques allow to elicit options in risky conditions that characterise the decision making process in the medical field.